Large‐scale metabolite quantitative trait locus analysis provides new insights for high‐quality maize improvement. (16th April 2019) - Li, Kun; Wen, Weiwei; Alseekh, Saleh; Yang, Xiaohong; Guo, Huan; Li, Wenqiang; Wang, Luxi; Pan, Qingchun; Zhan, Wei; Liu, Jie; Li, Yanhua; Wu, Xiao; et al.
Summary: It is generally recognized that many favorable genes which were lost during domestication, including those related to both nutritional value and stress resistance, remain hidden in wild relatives. To uncover such genes in teosinte, an ancestor of maize, we conducted metabolite profiling in a BC2 F7 population generated from a cross between the maize wild relative ( Zea mays ssp. mexicana ) and maize inbred line Mo17. In total, 65 primary metabolites were quantified in four tissues (seedling‐stage leaf, grouting‐stage leaf, young kernel and mature kernel) with clear tissue‐specific patterns emerging. Three hundred and fifty quantitative trait loci (QTLs) for these metabolites were obtained, which were distributed unevenly across the genome and included two QTL hotspots. Metabolite concentrations frequently increased in the presence of alleles from the teosinte genome while the opposite was observed for grain yield and shape trait QTLs. Combination of the multi‐tissue transcriptome and metabolome data provided considerable insight into the metabolic variations between maize and its wild relatives. This study thus identifies favorable genes hidden in the wild relative which should allow us to balance high yield and quality in future modern crop breeding programs. Significance Statement: A large scale QTL mapping of primary metabolite traits in a teosinte‐maize population reveals robust advantages existing in teosinte primary metabolism.